Diabetic Retinopathy. Morphofunctional State of the Retina in Pancreas Recipients - I. V. Vorobyeva; L. K. Moshetova; A. V. Pinchuk; E. V. Bulava; K. E. Lazareva; N. S. Zhuravel (Oftalʹmologiâ, 2021)
Diabetes mellitus (DM) is one of the most common and rapidly progressing diseases worldwide. Diabetic retinopathy (DR) is a common complication of diabetes and the main cause of vision loss in middle-aged and elderly people. The development and progression of DR is closely related to the duration of diabetes, hyperglycemia, and arterial hypertension. There is growing evidence that inflammation is one of the key links in the pathogenesis of diabetic retinal damage, but the exact molecular mechanisms remain to be known. Pancreas transplantation (PT) is currently the only effective treatment for diabetes that restores normal physiological glucose metabolism. Due to the limited number of PT surgeries associated with the severity of intra- and postoperative complications and the acute issue of organ donation, studies on the assessment of DR after PT are few and contradictory. There is a need for further studies of the DR state after PT with the study of the influence of risk factors, determination of the level of immunological markers and the use of modern instrumental research methods to create effective patient management regimens in the postoperative period.